Especiação química de íons metálicos em solução aquosa e as propriedades físico-químicas de nanotubos de aluminosilicatos – uma abordagem a partir da DFT e do método aproximado DFTB - Luciana Guimarães (2009)
The understanding of different processes related to environment, catalysis, chemistry, geochemistry, biology and nanomaterials has highlighted the importance of chemical speciation and attracted much attention of researchers. In this context, the chemical speciation of metal ions in aqueous solution, including hydration and hydrolyses processes, and the stability, structural and electronic properties of aluminosilicate nanotubes have been the subject of this thesis. Initially, it was investigated the hydrolysis processes of the transition metal ions Fe(III), Fe(II) and Mn(II) in aqueous solution (Chapter 3) and the first hydrolysis reaction of different transition metal ions (Chapter 4) by means of DFT/PCM methods. The results presented in Chapter 3 show that species of different geometries and coordination numbers are formed depending on the solution pH. The high spin ground state, sextet for Fe(III) and Mn(II) and quintet for Fe(II), has been obtained for all structures investigated, with the exception for cis-[Fe(OH)2(H2O)4] 1+ and cis- [Fe(OH)2(H2O)2] species which are quartet and triplet ground states, respectively. The results suggest that the combination of the DFT and UAHF/PCM methodologies with the first solvation shell treated explicitly is enough for describing the hydrolysis reactions of the Fe(III), Fe(II) and Mn(II) metal ions. The absolute mean error in the Gibbs free energy of the hydrolysis reaction is about 5 kcal/mol compared to the experimental values. The investigation of the first metal ion hydrolysis reactions was extended to the Ni(II), Cu(II), Fe(III), Fe(II), Mn(II), Co(II), Zn(II) and Al(III). The results presented in Chapter 4 show that DFT/PCM methodology is adequate to treat the fist hydrolysis of Ni(II), Cu(II), Fe(III), Fe(II) and Mn(II). However, it is observed that the Co(II), Zn(II) and Al(III) hydrolysis reaction were not well described. The results indicate that part of the success in the calculation of the equilibrium constants are due to the error canceling between the level of theory, the basis sets and the solvent model employed. Furthermore, the geometries obtained at gas phase, through quantum mechanical calculations have to represent the mean average of the structures found in the liquid phase. Following, in Chapter 5, the structural, electronic and mechanic properties of various chiralities and sizes of imogolite nanotubes were explored on the basis of the quantum mechanical approach SCC-DFTB. The results suggest the selectivity of a particular chirality, (12,0), in relation to the other nanotubes, which is different from conventional carbon and inorganic nanotubes. Furthermore, comparison of experimental and simulated XRD spectra as well as the energetic results clearly indicated the presence of only (12,0) imogolite nanotubes in experiments, even though it is not possible to exclude the presence of (10,0) nanotube. The mapped charge on the nanotube surfaces indicates the presence of positive charges on the outer region and negative charges on the inner region. Our results extend the theoretical understanding of this material and also provide a perspective of potential applications. The interest for the aluminosilicate behavior in the formation process of imogolite nanotubes has motivated us for the study developed in Chapter 6. In this step, it was carried out a study in order to contribute for the understanding (i) initial formation steps of aluminosilicate, in aqueous solution, and (ii) growing process and formation of imogolite nanotubes. Structural analysis indicate that the inclusion of ortosilicate group in the gibbsite hexagon formed by the Al atoms lead to distortions in the formed product. These results show that the deformation process of a flat imogolite like monolayer might be spontaneous. The results presented in this chapter are still preliminary even though they are important for understanding the initial steps of the aluminosilicates formation process. The challenge of studying systems in aqueous solution related to metal ions chemical speciation and clay nanostructures have permitted new applications of molecular modeling, and important information related to these processes have been gathered. This thesis contributes to the development of scientific knowledge of chemical speciation and clay nanomaterials areas. Besides, this knowledge is of great importance for innovative solutions in the areas of mineral technology and environment.